Functional And Humanistic Clues As Determinants of Consumer Loyalty: A Study of Fast Food Restaurant Business, Pokhara - Adhikari, Ujjwal (Journal of Interdisciplinary Studies, 2025)
Consumer experience is a determinant that assists in attaining the customer satisfaction, customer loyalty, and customer retention. The fast-food restaurant segment has been one of service sectors that has experienced unprecedented expansion due to the rising number of local and foreign visitors and the shifting lifestyle trend of urban consumers. The experience of the consumer is usually defined by the reaction to three main aspects of the dining experience the physical space, the service quality and behavior of staff, and the quality of food delivered. The main objective of this study is to identify the relationship between functional cues and humanistic cues on consumer loyalty in fast food restaurant business along with intermediating role of perceived quality. The research adopted a positivism paradigm and quantitative research design. The research was conducted through deductive approach by relying on existing theories and hypotheses. The sample size of 300 respondents was chosen by use of convenience sampling among the inhabitants of Pokhara. The respondents were the customers of fast food restaurants that are available within Pokhara valley. A structured questionnaire based on functional and humanistic cues was used to collect data. The mediation effect of perceived quality with consumer loyalty is analyzed. PLS-SEM was used to analyze the relationship between variables and verification of hypotheses of the suggested model. This study result indicated that Humanistic clues and Functional clues play a significant role in consumer loyalty. Whereas, the mediation effect of perceived quality between Humanistic clues and consumer loyalty is substantial but the mediation effect of perceived quality between Functional clues and consumer loyalty is non-significant. Thus, the study conclude that the customer retention and their positive word of mouth to the other customers relies on the way the service provider treat the customers and the quality and physical appearance of the products delivered to them.